2021
DOI: 10.1016/j.ijbiomac.2021.04.157
|View full text |Cite
|
Sign up to set email alerts
|

Chitin and chitosan as tools to combat COVID-19: A triple approach

Abstract: The progressive and fatal outbreak of the newly emerged coronavirus, SARS-CoV-2, necessitates rigorous collaboration of all health care systems and researchers from all around the world to bring such a devastating pandemic under control. As there is so far no officially approved drug or ideal vaccine for this disease, investigations on this infectious disease are actively pursued. Chitin and chitosan have shown promising results against viral infections. In this review, we first delve into the problematic cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 88 publications
0
50
0
Order By: Relevance
“…Recently, Sharma et al speculated the potential of using chitosan as a potential molecule against SARS-Cov-2 virus, the mechanism proposed being related to targeting CD 147 receptors, a novel route for invasion of the virus into cells [ 78 , 79 ].…”
Section: Pharmacological Potential Of Chitosan and Its Derivatives Applications In Current Pharmacotherapymentioning
confidence: 99%
“…Recently, Sharma et al speculated the potential of using chitosan as a potential molecule against SARS-Cov-2 virus, the mechanism proposed being related to targeting CD 147 receptors, a novel route for invasion of the virus into cells [ 78 , 79 ].…”
Section: Pharmacological Potential Of Chitosan and Its Derivatives Applications In Current Pharmacotherapymentioning
confidence: 99%
“…This capability of increasing the pharmacological action of an antimicrobial agent provides the opportunity for combination therapy in which chitosan acts as the effective excipient and simultaneously takes an active part in the treatment process. Apart from antifungal activity, chitosan has gained attention as an antiviral adjunctive directly impacting virus infectivity (Russo et al, 2014 ; Loutfy et al, 2020 ; He et al, 2021 ; Safarzadeh et al, 2021 ). In our previous studies, we observed that upon contact with vaginal fluid, chitosan creates a swellable hydrogel matrix which may serve as a barrier and additionally support mucosal tissue from the risk of infection (Szymanska et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 9 Based on our previous work on Conjugation of EGCG and Chitosan NPs, 8 a reasonable hypothesis would be to investigate the features and advantages of chitosan as a nano-carrier for antiviral drug delivery in the fight against recent (like COVID 19) and future coronaviruses. Very recently Safarzadeh et al 35 in a review article just published, have shown the potential applicability of chitin and chitosan to fight this overwhelming viral pandemic by overviewing the potential application of these materials in terms of their direct antiviral activities, the immune system associated effects and also as vehicles for targeted delivery of antiviral drugs. 35 …”
Section: Discussionmentioning
confidence: 99%